2013
DOI: 10.1007/s00520-013-1822-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-week home-based exercise program on the level of physical activity, insulin, and cytokines in colorectal cancer survivors: a pilot study

Abstract: CIHE program was as effective as IIHE program in increasing the level of PA, and the increase in PA resulted in significant change in HOMA-IR, IGF-1 axis, TNF-α, and adiponectin levels in stage II-III colorectal cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 36 publications
10
88
1
3
Order By: Relevance
“…Estos resultados coinciden con lo descrito por otros autores en pacientes con cáncer de mama, así como con otras localizaciones, tales como próstata 35 y colon 44 . Sin embargo, se requiere de estudios adicionales que favorezcan el consenso en la literatura científica acerca de los efectos y seguridad del ejercicio físico en estas pacientes.…”
Section: Figuraunclassified
“…Estos resultados coinciden con lo descrito por otros autores en pacientes con cáncer de mama, así como con otras localizaciones, tales como próstata 35 y colon 44 . Sin embargo, se requiere de estudios adicionales que favorezcan el consenso en la literatura científica acerca de los efectos y seguridad del ejercicio físico en estas pacientes.…”
Section: Figuraunclassified
“…The previous investigations showed a great share of obesity and lifestyle factors such as diet, cigarette smoking, alcohol consumption, and physical inactivity, in individual's susceptibility to CRC (Giovannucci, 2001;Chapelle, 2004). The effect of these etiological factors on the risk of CRC mediated through the insulin (INS) pathway (Giovannucci, 1995;Lee et al, 2013). Various studies have linked diabetes and CRC risk (Yang et al, 2004;Nagel et al, 2006;Chung et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since IGFI injection causes hypoglycemia, primarily by stimulating peripheral glucose uptake (32), and IGFBPs buffer the acute hypoglycemic effect of IGF-I (33), Nishida et al suggested that the alterations in IGF-IGFBP-3 levels might be an adaptive response to prevent hypoglycemia following exercise training (7). According to previous studies, IGFBP-3 level might decrease (16), increase (16,18,34), and remain unchanged (35-37) after exercise training. In study of Santa et al, IGFBP-3 increased in response to resistance training and decreased in response to aerobic training (16).…”
Section: Resultsmentioning
confidence: 83%
“…Some studies have reported that acute resistance and endurance exercise increase serum IGF-1 concentrations but do not affect serum IGFBP-3 levels (2, 10, 11). Although several studies have examined changes in circulating level of IGF-1 and IGFBP-3 in response to exercise training, the results of such studies have been inconsistent (12)(13)(14)(15)(16)(17)(18)(19). Moreover, overexpression of IGF-1 and IGFBP-3 is thought to increase tumor size in colorectal cancer (9, 20).…”
Section: Introductionmentioning
confidence: 99%